Influence of Predict-Observe-Explain Learning Model on Learning Outcomes of Class X SMA Students on Material of Chemical Bonds Related to Daily Life - Elisabet Manalu; Ajat Sudrajat (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This study aims to determine whether the learning outcomes and learning activities of students who are taught with the POE model associated with everyday life are higher than the learning outcomes with the conventional model on the material of Chemical Bonding. The research sample was an experimental class using the POE (Predict - Observe - Explain) learning model totaling 34 students and a control class using the conventional model totaling 34 students. The results of data analysis obtained, Students who learned with the POE model in the experimental class achieved an average score of 81.05, while students in the control class using the conventional model got an average score of 74.42. Based on a significance level of 0.05 and a degree of freedom of 32, a ttable value of 2.036 was obtained. The calculation results show that the tcount value of 2.80 is greater than ttable (2.80> 2.036) causing the null hypothesis (H₀) to be rejected and the alternative hypothesis (Hₐ) to be accepted. Because the value of rₓᵧ > rtable (0.885 > 0.339), then the null hypothesis (H₀) is rejected, meaning there is a positive correlation between learning activities and student learning outcomes who follow learning with the POE model. And data was obtained from 34 respondents regarding the effectiveness of the POE model of responses with the assessment criteria that have been set, the percentage reached 75% indicating the effectiveness and feasibility of using the POE model in the learning process.